2020
DOI: 10.1021/acs.orglett.0c02947
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(II)-Catalyzed Oxygen Transfer Reaction of N-Vinyl Nitrones to Prepare 2-(Pyridin-2-yl)ethanols

Abstract: A nickel­(II)-catalyzed oxygen transfer reaction of dibenzylideneacetone-derived N-vinyl-α,β-unsaturated nitrones has been identified for the preparation of polysubstituted 2-(pyridin-2-yl)­ethanols in good yields with high atom economy. The scope of the method is described, and mechanistic experiments are discussed. The reaction was easily performed at gram scales, and pyrido­[2,3-c]­carbazole was obtained in moderate yield over three steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…amine 9 mediated by copper, 11 and nickel-mediated formation of the pyridine ring using N-vinyl nitrones 10 (Scheme 1). 12 Installation of a 2-aryl group on a pyridine moiety is usually achieved through reaction of pyridine N-oxides 13 with Grignard reagents, 14,15 and from arylboronic acids by Suzuki-Miyaura coupling. 16 In this study, a series of 2-arylsubstituted 7,8-dihydroquinolin-6(5H)-ones were prepared by a novel, facile, and metal-free methodology and the potential of the obtained 2-aryl-7,8-dihydroquinolin-6(5H)ones as cytotoxic agents was evaluated against a cell line panel.…”
Section: Paper Synthesismentioning
confidence: 99%
“…amine 9 mediated by copper, 11 and nickel-mediated formation of the pyridine ring using N-vinyl nitrones 10 (Scheme 1). 12 Installation of a 2-aryl group on a pyridine moiety is usually achieved through reaction of pyridine N-oxides 13 with Grignard reagents, 14,15 and from arylboronic acids by Suzuki-Miyaura coupling. 16 In this study, a series of 2-arylsubstituted 7,8-dihydroquinolin-6(5H)-ones were prepared by a novel, facile, and metal-free methodology and the potential of the obtained 2-aryl-7,8-dihydroquinolin-6(5H)ones as cytotoxic agents was evaluated against a cell line panel.…”
Section: Paper Synthesismentioning
confidence: 99%
“…同年, 该小组 [40] 在此基础上以 N-烯基-α,β-不饱和 20 Proposed mechanism of constructing ninemembered heterocycles endoperoxides from N-vinyl-α,βunsaturated nitrones through visible light 2.2.2 N-烯基-α,β-不饱和硝酮构建吡啶化合物 2018 年, 莫冬亮课题组 [41] 2020 年, 该课题组 [43] 还发展了镍催化 N-烯基-α,β-不饱和硝酮的分子内氧转移反应, 合成了多取代吡啶醇 化合物 69. 通过该方法经三步反应以 36%产率得到吲 哚生物碱类化合物.…”
Section: N-烯基-αβ-不饱和硝酮与亚甲基环丙烷发生[3+2]环加unclassified
“…Nitrones, as extensively used 1,3-dipoles, have served as powerful reagents to access various significant azaheterocycles by cycloaddition reaction . In recent years, N -vinyl nitrone has been received much attention because of their ease in further transformations, such as electrocyclization, O -transfer reaction, and cycloaddition reaction . Based on the studies of N -vinyl nitrones in our group, we found that N -vinyl-α,β-unsaturated nitrones could participate in cycloaddition/rearrangement to access nine-membered azahetereocycles by reacting with various electrophiles .…”
mentioning
confidence: 99%